Comparison of diagnostic methods of malaria by peripheral smear, centrifuged buffy coat smear and rapid antigen detection test - Vora, Bhavnaben A.; Bindu, Rajan S. (International Journal of Research in Medical Sciences, 2017)
Background: Malaria is common, life threatening infection in endemic area and presents diagnostic challenge to laboratories in most endemic areas. A rapid and accurate diagnosis is a pre requisite for effective treatment, especially for potentially fatal cases of falciparum infection. Methods: Total 200 patients presented with fever and chills, were taken for study and performances of peripheral blood and centrifuged buffy coat smear were compared against the result of rapid antigen detection test (standard method). Results: out of 200 cases, 55 were positive by rapid detection test.30 of P. vivax, 24 of P. falci and 1 was mixed infection. Peripheral smear had 85.5% sensitive and 100% specific compared to RDT which was 100 % sensitive and specific whereas centrifuged buffy coat was 92.7% sensitive and 99.3% specific. Conclusions: Easy, rapid, most sensitive and specific diagnostic method will help in early diagnosis and lead to decrease in morbidity and mortality.